Randomized, Double-Blind, Phase III Study of Fosnetupitant Versus Fosaprepitant for Prevention of Highly Emetogenic Chemotherapy-Induced Nausea and Vomiting: CONSOLE. Issue 2 (10th January 2022) - Hata, Akito; Okamoto, Isamu; Inui, Naoki; Okada, Morihito; Morise, Masahiro; Akiyoshi, Kohei; Takeda, Masayuki; Watanabe, Yasutaka; Sugawara, Shunichi; Shinagawa, Naofumi; Kubota, Kaoru; Saeki, Toshiaki; et al.
Abstract : PURPOSE: We evaluated the efficacy and safety of fosnetupitant (FosNTP) versus fosaprepitant (FosAPR) for preventing highly emetogenic chemotherapy-induced nausea and vomiting. This phase III study was the first head-to-head comparison between two different neurokinin-1 receptor antagonists in combination with palonosetron and dexamethasone. PATIENTS AND METHODS: Patients scheduled to receive cisplatin-based chemotherapy were randomly assigned 1:1 to FosNTP 235 mg or FosAPR 150 mg in combination with palonosetron 0.75 mg and dexamethasone. The primary end point was overall (0-120 hours) complete response (CR; no emetic event and no rescue medication) rate, stratified by sex and age category, to show the noninferiority of FosNTP to FosAPR (noninferiority margin, –10% for the difference in the overall CR rate). RESULTS: Overall, 795 patients were randomly assigned, of whom 785 received the study drug (FosNTP [N = 392] v FosAPR [N = 393]) and were evaluated for efficacy and safety. The overall CR rate was 75.2% versus 71.0%, respectively (Mantel-Haenszel common risk difference, 4.1%; 95% CI, –2.1% to 10.3%), demonstrating noninferiority of FosNTP to FosAPR. The CR rates in the acute (0-24 hours), delayed (24-120 hours), and beyond delayed (120-168 hours) phases, and at 0-168 hours were 93.9% versus 92.6%, 76.8% versus 72.8%, 86.5% versus 81.4%, and 73.2% versus 66.9%, respectively. The incidence rates of treatment-related adverse events with FosNTP versus FosAPR were 22.2% versus 25.4%, whereas adverse events or treatment-related adverse events relevant to injection site reactions were 11.0% versus 20.6% ( P < .001) and 0.3% versus 3.6% ( P < .001), respectively. CONCLUSION: FosNTP demonstrated noninferiority to FosAPR, with a favorable safety profile and lower risk for injection site reactions. Thus, FosNTP is valuable in the prophylaxis of acute, delayed, and beyond delayed chemotherapy-induced nausea and vomiting. Abstract :